Conflicting purchasers and users appeal toward a design goal determining children and parent purchasing decision: a case of toy packing design - Wichanat Tiwasing; Nopadon Sahachaisaeree (My University, 2010)
Conflicting design goals for users who are not purchasers such as toys and baby products is obviously a greater challenge for packaging design. Using computer game as a case study, this research derives an optimal design strategy to respond to the conflicting goals between that of users and purchasers. In the present initial stage of research tool development, the study found that a number of contradictory on preferences between children and parents existed. Most research tools are proved valid with small flaw to be corrected. Additional indicators on perceived affordance, safety, and value should be added for comparison reasons.
Keywords: Value (mathematics); Affordance; Research Design; Consumer Packaging Perceptions and Trends